Photospheric activity, rotation, and star-planet interaction of the planet-hosting star CoRoT-6 - Lanza, A; Bonomo, A; Pagano, I; Leto, G; Messina, S; Cutispoto, G; Moutou, C; Aigrain, S; Alonso, R; Barge, P; Deleuil, M; Fridlund, M; et al. (2010)
The CoRoT satellite has recently discovered a hot Jupiter that transits across the disc of a F9V star called CoRoT-6 with a period of 8.886 days. We model the photospheric activity of the star and use the maps of the active regions to study stellar differential rotation and the star-planet interaction. We apply a maximum entropy spot model to fit the optical modulation as observed by CoRoT during a uninterrupted interval of about 140 days. Photospheric active regions are assumed to consist of spots and faculae in a fixed proportion with solar-like contrasts. Individual active regions have lifetimes up to 30-40 days. Most of them form and decay within five active longitudes whose different migration rates are attributed to the stellar differential rotation for which a lower limit of Δ Ω / Ω = 0.12 ± 0.02 is obtained. Several active regions show a maximum of activity at a longitude lagging the subplanetary point by about 200 degrees with the probability of a chance occurrence being smaller than 1 percent. Our spot modelling indicates that the photospheric activity of CoRoT-6 could be partially modulated by some kind of star-planet magnetic interaction, while an interaction related to tides is highly unlikely because of the weakness of the tidal force.